Impact of chemoradiotherapy for first primary lung cancer on the prognosis and re-chemoradiotherapy sensitivity of second primary lung cancer - Chen, Zhe; Wang, Gaoming; Wang, Nan; Liu, Jiangjiang; Yao, Yu; Ma, Haitao; Luo, Jing; Xie, Kai (Frontiers in Immunology, 2025)
BackgroundDespite undergoing surgery and chemoradiotherapy, patients with first primary lung cancer (FPLC) remain at risk for second primary lung cancer (SPLC), which is associated with a poor prognosis. The effects of FPLC chemoradiotherapy on SPLC prognosis and its sensitivity to re-chemoradiotherapy have not been adequately investigated.MethodsThis cohort study analyzed data from 23,827 patients who underwent FPLC surgery during 1973–2021, drawn from the Surveillance, Epidemiology, and End Results database. Among these, 5,302 FPLC patients developed SPLC within 5 years of their initial diagnosis. We employed the Fine-Gray competitive risk model, Cox proportional hazards model, and restricted mean survival time analysis to assess the effects of FPLC radiotherapy and chemotherapy on SPLC risk and survival differences.ResultsThe competitive risk model indicated that FPLC radiotherapy and chemotherapy did not significantly change the risk of developing SPLC. However, the Cox proportional hazards model revealed that FPLC radiotherapy was associated with decreased overall survival (OS; HR=1.251, P<0.001) and cancer-specific survival (CSS; HR=1.228, P=0.001) in patients with SPLC. Conversely, FPLC chemotherapy was linked to improved OS (HR=0.881, P=0.012) in this population. Patients with SPLC who received combined chemoradiotherapy for FPLC exhibited significantly reduced survival times (OS: HR=1.157, P=0.030; CSS: HR=1.198, P=0.018), a finding confirmed across multiple models. For SPLC patients with prior FPLC chemoradiotherapy, subsequent SPLC radiotherapy significantly improved prognosis. Notably, this benefit is even more pronounced in patients who have not received prior chemoradiotherapy. While SPLC chemotherapy enhanced OS for patients who did not receive FPLC chemotherapy, it was associated with reduced CSS for those who had.ConclusionsOverall, FPLC chemoradiotherapy influences SPLC prognosis and influences sensitivity to treatment. Tailoring SPLC management to FPLC treatment regimens may improve survival outcomes.